Analysis of Leading Sectors Against Economic Growth in Merauke Regency 2016-2020 - Marthen A. I Nahumury; Fenty Y. Manuhutu (GoAcademica Research & Publishing, 2022)
The purpose of this study was to determine the level of economic growth and the factors that influence the leading sector in Merauke Regency in 2016-2020. This study used a quantitative method using Location Quotiens (LQ) analysis tools and conducted research in Merauke Regency, to determine and find the leading sectors in 2016-2020. The results of my research show that there are several factors contained in the economic growth of nine sectors, there are 6 main base sectors in Merauke Regency in 2016-2020, namely agriculture, transportation, information and communication, finance, rental, corporate services, processing industry, services, trade, hotels, and restaurants. These six leading sectors will become the leading sectors for the non-base sector in order to be able to develop.